Contemporary Development and Religious Modernization - Nazri Adlani Harahap; Muhammad Sofwan; Pangulu Abdul Karim (Educare: Journal Educational and Multimedia, 2024)
The era of digitalization and technological developments that accompany humans in this century have certainly resulted in various kinds of polemics in society, especially in religious communities, the threat of orthodoxy, radicalism and pluralism in the midst of the various religions embraced by humans and bridges between generations that are not yet connected to each other which results in the delivery of religious teachings among young people that they consider as old-fashioned teachings that do not follow the development of the times and seem monotonous. Therefore, it is important for religion to also follow the development of the times, especially the delivery that includes contemporary modernization in conveying religious teachings.